STORE ATMOSPHERE SEBAGAI STRATEGI DALAM MENINGKATKAN DAYA TARIK WISATA DI TANABAMBU, BOGOR - Vanessa Delfia Sanjaya; Prayogo Susanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The tourism sector plays a crucial role in the country's economy by introducing regional culture to both local and international tourists. This study was conducted in Tanabambu, Bogor, and aimed to analyze the appropriate strategy for implementing store atmosphere as a strategy to enhance tourism appeal in Tanabambu, Bogor. Tanabambu has a unique concept based on nature and culture that has the potential to be developed as a tourist attraction. The research method used in this study is a qualitative approach with data collection methods using observation, interviews, documentation, and literature studies. Research informants were determined using the Quadruple Helix model that uses management, visitors, academics, and the government as sources of information. Data analysis used SWOT analysis and SWOT Matrix, IFAS and EFAS Matrix, and 4-quadrant SWOT Matrix as methods for formulating strategies. The results showed that the store atmosphere elements in Tanabambu, consisting of the store exterior, general interior, store layout, and interior display, can create an interesting experience for visitors. The concept of Tanabambu, traditional decoration, and a comfortable atmosphere are the main factors in enhancing tourist appeal. However, the use of store atmosphere as a strategy is still not optimal and requires further development. In conclusion, store atmosphere plays a crucial role as a strategy in enhancing tourist appeal. Therefore, more targeted development is needed to maximize Tanabambu's potential as a culinary tourism destination in Bogor.